2022
DOI: 10.1002/tox.23460
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine formula T33 inhibits the proliferation of human colorectal cancer cells by inducing autophagy

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related death globally. Although surgery is still the major method for CRC therapy, the adoption of alternative treatments, such as traditional Chinese medicine (TCM), for CRC treatment is increasing.Our previous study has indicated the anti-breast cancer activity of T33 (a TCM formula). Interestingly, a major ingredient in T33, Baishao (Paeoniae Radix Alba), was reported to have antiproliferative effects on CRC cells. Therefore, this study further validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Such as inhibition of autophagy leading to regression of pancreatic cancer ( 66 ) and lung cancer ( 67 ) suggests a role for autophagy in sustaining tumor growth. While the induction of autophagy in renal cell cancer ( 68 ), colorectal cancer ( 69 ) inhibits cell proliferation, suggesting that excessive autophagy can limit cell growth. Our data and others suggest that significant deviations from the physiological set point of basal autophagy, either high or low, can lead to cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Such as inhibition of autophagy leading to regression of pancreatic cancer ( 66 ) and lung cancer ( 67 ) suggests a role for autophagy in sustaining tumor growth. While the induction of autophagy in renal cell cancer ( 68 ), colorectal cancer ( 69 ) inhibits cell proliferation, suggesting that excessive autophagy can limit cell growth. Our data and others suggest that significant deviations from the physiological set point of basal autophagy, either high or low, can lead to cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy is the immune-enhancement effect of CH [ 70 , 71 ], which maintains the functional gut immunity for necessary pathogen recognition and elimination. Complications: ① a broad array of investigations have reported the antitumor effect of BT [ 72 ], PP [ 73 ], BD [ 74 76 ], CH [ 77 , 78 ], LC [ 79 , 80 ], SK [ 81 83 ], and CWT [ 84 , 85 ], which is considered a major complication of UC. Based on TCGA database, the targets of JW clustered COAD patients into two groups and correlated with the survival probability.…”
Section: Discussionmentioning
confidence: 99%
“…Complications: ① a broad array of investigations have reported the antitumor effect of BT [ 72 ], PP [ 73 ], BD [ 74 76 ], CH [ 77 , 78 ], LC [ 79 , 80 ], SK [ 81 83 ], and CWT [ 84 , 85 ], which is considered a major complication of UC. Based on TCGA database, the targets of JW clustered COAD patients into two groups and correlated with the survival probability.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that melatonin, 11 dichlorodiphenyltrichloroethane, 12 xiaotansanjiefang, 13 traditional Chinese medicine formula T33, 14 and some active ingredients and extracts of traditional Chinese medicine, such as xanthohumol, 15 hinokitiol, 16 bergapten, 17 lupeol, 18 tribulus terrestris fruit extract, 19 momordica balsamina crude acetone extract, 20 and crude extract of Rheum palmatum L 21,22 showed the anti‐cancer activity in colorectal cancer. In addition, the leguminous plant sophora flavescens has been used for more than 2000 years, as a traditional Chinese medicine, and matrine, an alkaloid, was extracted from it and exerted multiple pharmacological effects, such as antiviral, diuretic, anti‐inflammatory and anti‐allergic effects 23,24 .…”
Section: Introductionmentioning
confidence: 99%